2017
DOI: 10.1007/s40279-017-0780-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Knee Injury in Golf: A Systematic Review

Abstract: Background Golf is commonly considered a low-impact sport that carries little risk of injury to the knee and is generally allowed following total knee arthroplasty (TKA). Kinematic and kinetic studies of the golf swing have reported results relevant to the knee, but consensus as to the loads experienced during a swing and how the biomechanics of an individual's technique may expose the knee to risk of injury is lacking. Objectives Our objective was to establish (1) the prevalence of knee injury resulting from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…Knee joint angles were calculated using an X-Y-Z Cardan sequence (flexion/extension [X], abduction/adduction [Y], internal/external rotation [Z]). External knee moments were also calculated in Visual 3D with the shank as the reference segment and were normalised to the participant's body mass (Lynn & Noffal, 2010;Baker et al, 2017). Positive joint angles around the X, Y and Z axes represented flexion, abduction and external rotation of both knees.…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Knee joint angles were calculated using an X-Y-Z Cardan sequence (flexion/extension [X], abduction/adduction [Y], internal/external rotation [Z]). External knee moments were also calculated in Visual 3D with the shank as the reference segment and were normalised to the participant's body mass (Lynn & Noffal, 2010;Baker et al, 2017). Positive joint angles around the X, Y and Z axes represented flexion, abduction and external rotation of both knees.…”
Section: Data Processingmentioning
confidence: 99%
“…It is also important to consider how moments and movements of the lower limb joints could contribute to injuries (Marshall & McNair, 2013). A recent systematic review reported that 3-18% of golfing injuries occurred at the knee, however the reviewed studies gave little information on the exact nature of the injuries or which knee was affected (Baker et al, 2017). Baker et al stated that although golf is considered a 'low-impact' sport, the prevalence of knee injuries was comparable to high-impact sports such as basketball.…”
Section: Introductionmentioning
confidence: 99%
“…Many reviews have been published on golf analysis, including seven focused on health matters: three on low-back pain [9][10][11], one on knee injuries [12], two on injuries in general [3,13], and one on the link between health and golf [2]. Another study focused on electromyographic activity (EMG) measurements during the golf swing [14], with the objective of identifying more activated muscle groups.…”
Section: Introductionmentioning
confidence: 99%
“…Knee joint injuries are common in physical training, and some injuries are irreversible ( 1 ). Different forms of motion can cause different knee joint injuries due to different knee joint mechanics ( 2 , 3 ). Studies have found that the incidence of knee joint pain is significantly higher in people who regularly train on long-distance walking ( 4 ), and accumulated high-intensity walking training can directly lead to meniscus injury ( 5 ).…”
Section: Introductionmentioning
confidence: 99%